CALIDAD DEL SERVICIO AL USUARIO DEL DISPENSARIO POTOSÍ DEL SEGURO SOCIAL CAMPESINO” - FAJARDO COELLO, JUAN OSWALDO (2018)
The present case study seeks to know what opinion users of the dependencies of the Potosí Dispensary of the Rural Social Security, on the services that receives within the unit to determine in what areas of care there are problems or greater difficulties proposing the most appropriate and feasible solution possible to minimize the dissatisfaction of the users of the service provided by the unit medical